ANALYSIS OF MATERIAL NEEDS AND TRAINING METHODS FOR VILLAGE OWNED ENTERPRISES MANAGER AS AN EFFORT TO INCREASE THE CAPACITY OF HUMAN RESOURCES IN TANANTOVEA SUB-DISTRICT, DONGGALA DISTRICT - Yusuf, Muhammad; Kaseng, Saharuddin; Evvy Rossanti, Niluh Putu (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2022)
This research analyzes the management conditions, constraints, material requirements, and training methods for managing Village-Owned Enterprises (BUM Desa) in Donggala District. This research uses quantitative and qualitative methods (mix methods), the quantitative method used is Importance Performance Analysis (IPA) analysis in mapping the capacity of 10 Village-Owned Enterprises, and qualitative methods are used to describe the factual conditions of Village-Owned Enterprises management by selecting 12 informants consisting of village government officials, administrators of Village-Owned Enterprises, and Village Facilitators. The results indicate that performance is still low. However, the importance is high, namely (1) The managerial process of Village-Owned Enterprises, (2) Marketing methods and strategies, (3) Human Resources recruitment and qualification process, (4) Management knowledge, ( 5) Skills in managing a business, and (6) Strengthening the capacity of Village-Owned Enterprises management. At the research location, only Boya Paramba Mandiri Village-Owned Enterprises in Nupabomba Village, one of whose business activities can contribute to the economic improvement of the coffee farming community in Nupabomba Village. Constraints faced in managing Village-Owned Enterprises, namely related to the system and institutional support, personnel in the organization have not carried out their duties and functions optimally, and human resource factors in managing business management. Keywords: Human Resource Capacity, Village-Owned Enterprises, Management, Training